2016
DOI: 10.1242/jeb.123992
|View full text |Cite
|
Sign up to set email alerts
|

The role of the antioxidant system during intense endurance exercise: lessons from migrating birds

Abstract: During migration, birds substantially increase their metabolic rate and burn fats as fuel and yet somehow avoid succumbing to overwhelming oxidative damage. The physiological means by which vertebrates such as migrating birds can counteract an increased production of reactive species (RS) are rather limited: they can upregulate their endogenous antioxidant system and/or consume dietary antioxidants ( prophylactically or therapeutically). Thus, birds can alter different components of their antioxidant system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 152 publications
(257 reference statements)
0
79
1
Order By: Relevance
“…The accumulation of oxidative damage from the byproducts of aerobic metabolism is expected to reduce whole‐animal performance either directly, through reduced cellular and organismal function (Eikenaar, Isaksson, & Hegemann, ), or indirectly, as resources are directed to endogenous antioxidant responses rather than oxidative capacity (Cooper‐Mullin & McWilliams, ; Larcombe, Herborn, Alexander, & Arnold, ). The potential for reduced performance is particularly high for individuals with high tissue PUFA concentrations, due to elevated risk of peroxidation (Hulbert, ; Skrip & McWilliams, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accumulation of oxidative damage from the byproducts of aerobic metabolism is expected to reduce whole‐animal performance either directly, through reduced cellular and organismal function (Eikenaar, Isaksson, & Hegemann, ), or indirectly, as resources are directed to endogenous antioxidant responses rather than oxidative capacity (Cooper‐Mullin & McWilliams, ; Larcombe, Herborn, Alexander, & Arnold, ). The potential for reduced performance is particularly high for individuals with high tissue PUFA concentrations, due to elevated risk of peroxidation (Hulbert, ; Skrip & McWilliams, ).…”
Section: Discussionmentioning
confidence: 99%
“…This negative result could be the product of a low accumulation of oxidative damage from flight training and/or the high‐PUFA diet as was found in a previous wind tunnel study (Dick & Guglielmo, ), although the variance in PUFA content of the diets in that study was much smaller. It is also possible that the hydrophilic antioxidants used to supplement the diets simply did not remain in circulation at high enough concentrations to prophylactically counter oxidative damage and failed to support recovery from oxidative damage (Beaulieu & Schaefer, ; Cooper‐Mullin & McWilliams, ). One other speculative explanation is that endogenous antioxidants such as uric acid (Alan & McWilliams, ; Machin, Simoyi, Blemings, & Klandorf, ) could be preferentially used to counter high RS production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Jimenez et al (2013), we have previously found that primary fibroblasts from tropical birds cell lines are more resistant to damage chemically ensued by cadmium, H 2 O 2 , paraquat, tunicamycin and methane methylsulfonate compared with temperate bird cell lines. It is known that during times of stress, such as migration, birds can upregulate aspects of their antioxidant system to compensate for the increase in oxidative stressors (Cooper-Mullin and McWilliams 2016). It is known that during times of stress, such as migration, birds can upregulate aspects of their antioxidant system to compensate for the increase in oxidative stressors (Cooper-Mullin and McWilliams 2016).…”
Section: Discussionmentioning
confidence: 99%